Knowledge Mapping of Volunteer Motivation: A Bibliometric Analysis and Cross-Cultural Comparative Study - Chen, Jing; Wang, Chengliang; Tang, Yulong (Frontiers in Psychology, 2022)
Volunteers play an indispensable role in several major events and activities. The purpose of this study is to review studies on volunteer motivation from 2000 to 2021 and to discover the development trends in this field. The Web of Science Core Collection is the main literature data resource, from which 162 papers on volunteer motivation published in the SSCI were selected. Using two visualization analysis tools, CiteSpace and VOSviewer, this study conducts bibliometric analysis and systematic review from multiple dimensions, identifying the authors, countries, institutions, and journals with high productivity in this field. Additionally, we explored highly cited papers, authors, and journals in this field. This study aims to find the research hotspots and theoretical basis through co-occurrence analysis and cluster analysis of keywords and explore the evolution through the time zone map drawn with CiteSpace. Moreover, we focus on the influence of Chinese and Western cultures (represented by China and the United States) on volunteer motivation. It was found that Chinese volunteers were more affected by collectivism, whereas American volunteers were more affected by individualism. The conclusion of this study constructs a clear framework for research on volunteer motivation, which provides researchers with a deeper and thorough understanding of the connotation of volunteer motivation, providing guidance and support for future research in this field.